2004
DOI: 10.1111/j.1469-8749.2004.tb00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered pathways for auditory discrimination and recognition memory in preterm infants

Abstract: Preterm infants are at increased risk for cognitive disorders, including impairments in recognition memory. This study evaluated the effects of extreme prematurity on the neural pathway for auditory recognition memory using event‐related potentials (ERPs), a neurophysiological technique widely used in cognitive neuroscience. ERPs were recorded at term postmenstrual age in 35 preterm infants born at less than 32 weeks’gestation (22 males, 13 females; mean birthweight ([BW] 1154g, SD 374g) with normal brain ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…In addition, a negative correlation was observed between cortical activity in response to IDS and PNA in the right temporal area (see Figure 5). This finding is consistent with previous ERP studies showing that altered neural response for processing speech sounds such as syllable or consonant changes occurs in preterm infants at term-equivalent age (Therien et al, 2004; Key et al, 2012). With the higher spatial resolution of multichannel NIRS, the present data supports these findings and suggests that increasing PNA in preterm infants was associated with decreased oxy-Hb changes with speech in the right temporal region, despite greater postnatal experience.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, a negative correlation was observed between cortical activity in response to IDS and PNA in the right temporal area (see Figure 5). This finding is consistent with previous ERP studies showing that altered neural response for processing speech sounds such as syllable or consonant changes occurs in preterm infants at term-equivalent age (Therien et al, 2004; Key et al, 2012). With the higher spatial resolution of multichannel NIRS, the present data supports these findings and suggests that increasing PNA in preterm infants was associated with decreased oxy-Hb changes with speech in the right temporal region, despite greater postnatal experience.…”
Section: Discussionsupporting
confidence: 93%
“…Preterm infants at term-equivalent age are likely to have less intrauterine auditory experience than full-term neonates. In fact, preterm infants at term exhibited no difference in ERP in response to the mother’s and strangers’ voices despite longer postnatal exposure to the maternal voice (Therien et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified these cortical regions as sensitive to the mother's voice (Beauchemin et al, 2010;Dehaene-Lambertz et al, 2010;Siddappa et al, 2004;Therien et al, 2004). Furthermore, each EEG electrode was linked to an earlobe reference electrode at A2, and these signals were sampled at 1,000 Hz and filtered with a 50-or 60-Hz notch filter to suppress noise from alternating current power sources.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…Second, we needed another new measure to investigate the cortical functions related to the changes in RR. In the previous studies, slow latency components in several kinds of EEG such as Nc and PSW were measured as activities of the cortical attentional function (e.g., Richards, 2003;Siddappa et al, 2004;Therien, Worwa, Mattia, & deRegnier, 2004). These slow latency components correspond to the amplitude of EEG delta waves (.5-4 Hz).…”
Section: Introductionmentioning
confidence: 99%